Penerapan SPK Pengangkatan Karyawan Menggunakan Metode MOORA Pada Rumah Sakit Setio Husodo - Mita Hul Jannah; Nuriadi Nuriadi; Tika Christy (LPPM STMIK Royal Kisaran, 2022)
Abstrack : Setio Husodo Hospital is an institution engaged in the field of health services. At Setio Husodo Hospital, there are 2 categories of employees, namely employees of medical staff and employees of management and hospital services. Therefore, Setio Husodo Hospital always conducts a probationary period (training) for 3 months for each new employee who enters. In appointing new employee candidates, an appropriate selection and observation process is needed during the probationary period to maximize the quality of these prospective employees, but in the current information and technology era, it turns out that there are still several agencies and companies that are processing their data using the following methods: manual including Setio Husodo Hospital. Currently there are 144 employees at Setio Husodo Hospital, 15 General Practitioners and 9 Specialist Doctors. During the past 1 year there have been 26 new employees who have been accepted and become permanent employees.Keywords : hospital; employee; SPK; training; agency Abstrak : Rumah sakit setio husodo merupakan instansi yang bergerak di bidang pelayanan kesehatan. Pada Rumah sakit setio husodo terdapat 2 katagori karyawan yaitu karyawan tenaga medis dan karyawan bagian majemen maupun pelayanan Rumah sakit. Oleh karena itu Rumah Sakit Setio husodo selalu melakukan masa percobaan (training) selama 3 bulan pada setiap karyawan yang baru masuk. Dalam pengangkatan calon karyawan baru dibutuhkan proses seleksi dan pengamatan yang tepat saat masa percobaan untuk memaksimalkan kualitas dari para calon karyawan tersebut, namun dalam era informasi dan teknologi yang semakin berkembang saat ini ternyata masih ada beberapa instansi dan perusahan yang dalam proses pengolahan datanya dengan menggunakan cara manual termasuk Rumah Sakit Setio Husodo. Saat ini karyawan yang ada di Rumah Sakit Setio Husodo sebanyak 144 karyawan, 15 Dokter Umum dan 9 Dokter Spesialis. Selama 1 tahun belakangan terdapat 26 Karyawan baru yang sudah diterima dan menjadi karyawan tetap. Kata Kunci : rumah sakit; karyawan; SPK; traning; instansi